The International Space Station - Branley, Franklyn Mansfield, 1915-2002.; Kelley, True ([New York] : HarperCollins, 2000)
Explains the construction and purpose of the International Space Station and the life of the astronauts on board.
Book Links (A.L.A.).
School Library Journal.
Wilson's Children.
3.0
K-3
Keywords: International Space Station -- Juvenile literature; International Space Station; International Space Station; Space stations